Climate‐driven habitat change causes evolution in Threespine Stickleback. (21st November 2019) - Des Roches, Simone; Bell, Michael A.; Palkovacs, Eric P.
Abstract: Climate change can shape evolution directly by altering abiotic conditions or indirectly by modifying habitats, yet few studies have investigated the effects of climate‐driven habitat change on contemporary evolution. We resampled populations of Threespine Stickleback ( Gasterosteus aculeatus ) along a latitudinal gradient in California bar‐built estuaries to examine their evolution in response to changing climate and habitat. We took advantage of the strong association between stickleback lateral plate phenotypes and Ectodysplasin A ( Eda ) genotypes to infer changes in allele frequencies over time. Our results show that over time the frequency of low‐plated alleles has generally increased and heterozygosity has decreased. Latitudinal patterns in stickleback plate phenotypes suggest that evolution at Eda is a response to climate‐driven habitat transformation rather than a direct consequence of climate. As climate change has reduced precipitation and increased temperature and drought, bar‐built estuaries have transitioned from lotic (flowing‐water) to lentic (still‐water) habitats, where the low‐plated allele is favoured. The low‐plated allele has achieved fixation at the driest, hottest southernmost sites, a trend that is progressing northward with climate change. Climate‐driven habitat change is therefore causing a reduction in genetic variation that may hinder future adaptation for populations facing multiple threats. Abstract : Climate change is causing Threespine Stickleback in California estuaries to evolve fewer lateral bony plates due to changes in habitat conditions. As California's climate becomes hotter and drier, estuaries are transitioning from lotic (flowing‐water) to lentic (still‐water) habitats—an association that is also reflected along a latitudinal gradient, from the hotter, drier south to the cooler, wetter north. Because lentic habitats favour stickleback with fewer lateral plates, the frequency of low‐plated alleles has generally increased over time. The low‐plated allele has achieved fixation at the driest, hottest southernmost sites, a trend that is progressing northward with climate change.